2015
DOI: 10.1111/eth.12439
|View full text |Cite
|
Sign up to set email alerts
|

Is Foraging Time Limited During Winter? – A Feeding Experiment with Tree Sparrows Under Different Predation Risk

Abstract: Small passerines are faced with a trade-off when foraging during winter. Increasing energy reserves makes them more vulnerable to predators, while a low level of reserves exposes them to a high risk of starvation. Whether small birds under these circumstances are allowed to reduce their foraging activity under increased predation risk, for example in feeding sites more exposed to predators, remains controversial in former behavioural and ecological researches. In this study, we investigated the foraging activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Contrary to expectations, with more feeding bouts, the time lags between two successive feeding bouts were longer in the riskier condition (see Table 1 in Mónus & Barta 2011 for more details). This also underlies the role of perceived predation-risk in the time-budget pattern we observed (Mónus et al 2016). In that case, feeding interruptions contributed to the anti-predator strategy of the sparrows; however, misclassifications of social information on threats (i.e., false alarms) are also common and result in feeding interruptions (Lima 1994, Cresswell et al 2000, Beauchamp & Ruxton 2007.…”
Section: Feeding Interruptions and False-alarm Flights As Estimates Osupporting
confidence: 66%
“…Contrary to expectations, with more feeding bouts, the time lags between two successive feeding bouts were longer in the riskier condition (see Table 1 in Mónus & Barta 2011 for more details). This also underlies the role of perceived predation-risk in the time-budget pattern we observed (Mónus et al 2016). In that case, feeding interruptions contributed to the anti-predator strategy of the sparrows; however, misclassifications of social information on threats (i.e., false alarms) are also common and result in feeding interruptions (Lima 1994, Cresswell et al 2000, Beauchamp & Ruxton 2007.…”
Section: Feeding Interruptions and False-alarm Flights As Estimates Osupporting
confidence: 66%
“…Following recommendations of Remsen & Robinson [62], we defined an attack as the action of the bill striking or picking up an object. Vigilance rate is the proportion of time spent vigilant,which has been used as a proxy of predation risk since vigilance increases with predation risk [13, 43, 47]. Because antshrikes and antwrens forage low to the ground (<5 m), and forest-falcons ambush from the canopy, birds were considered vigilant when the bill was held horizontally or pointed upward [48, 65, 69].…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that the foraging attack rate (a proxy for resource availability [59, 63];), vigilance rate (a proxy for predation risk [13, 47];), and vegetation density surrounding the Dusky-throated Antshrikes would explain the space use of the flock. We predicted that Dusky-throated Antshrikes would have higher attack rates, lower vigilance rates, and forage in sparser vegetation density in high use areas of the flock compared to low-use areas.…”
Section: Introductionmentioning
confidence: 99%
“…For those studies that have quantified use of supplemental food, the great majority have been conducted in regions with continental climates that are characterized by cold winters with extensive snow cover and temperatures below freezing (Bonter, Zuckerberg, Sedgwick, & Hochachka, 2013;Cooper & Sonsthagen, 2007;Kessel, 1976;Lima, 1985;Wilson, 2001). Several studies have found that feeder use by songbirds in midwinter, when ambient temperatures reach seasonal lows and foraging time is constrained by short photoperiods, generally increased throughout the day until sharply declining as sunset approached and individuals moved to roost sites (Bonter et al, 2013;Monus & Barta, 2016). Feeder use by songbirds in continental climates has also been found to increase with decreasing ambient temperature (Bonter et al, 2013;Chaplin, 1976;Zuckerberg et al, 2011), and decrease with increasing wind speed (Kessel, 1976;Kubota & Nakamura, 2000), with both patterns thought to be driven by the energetic needs of birds in winter (Bednekoff & Houston, 1994;McNamara, Houston, & Lima, 1994).…”
Section: Introductionmentioning
confidence: 99%